Association of Uric Acid Level and Body Mass Index in Type 2 Diabetes Mellitus Patients. - Maya savira (Talenta Publisher Universitas Sumatera Utara, 2020)
Body Mass Index (BMI) or formerly called Quetelet Index is the measurement for scoring nutrient state in adults by using body weight (in kilogram) and body height (in metre). Obesity and overweight are defined as an abnormality of fat accumulation that can damage our health. Uric acid is a substance that is formed when the breaking process of purine occur. Hyperuricemia are condition that are closely related with gout. Uric acid level increased significantly towards those having obesity. It is also concluded that obesity was the usual cause in patients with recurrent gout attack. Strong relation has been found between high BMI with gout arthritis occurance. This research is a descriptive analytic research with cross sectional design included 50 diabetic subjects aged over 40 years old. Subjects picked by consecutive sampling then we examined the weight, height, waist size, blood pressure and laboratory tests for fasting blood sugar and serum uric acid level. With statistical analysis using chi square we found that there was no significant association between BMI and serum uric acid level in type 2 diabetes mellitus patients (p>0.005).